Investigation of delamination at exit of drilled carbon fiber reinforced polymer (CFRP) composite with diamond coated ball nose drills - Konneh, Mohamed; Abdallah, Kassim Abdulrahman; Sudin, Izman; Jusoh, Mohd Amirudin (Trans Tech Publications Ltd., Switzerland, 2015)

(untitled)
The investigation of the influence of machining parameters on delamination at exit of drilled holes after drilling into CFRP composite using 4 mm-diameter 2-fluted carbide drills coated diamond is present in this paper. The delamination at tool exit was analyzed in terms of delamination factor on the basis of analysis of variance (ANOVA) of Central Composite Design (CCD) of experiments. It is found that spindle speed is the most influential factor for the drilling of CFRP within the range of cutting parameters examined. The lowest delamination factor (1.003) was generated at rotational speed, 5063 rpm and feed rate, 180 mm/min; and the highest delamination factor (1.093) generated at rotational speed, 537 rpm and feed rate, 180 mm/min. A mathematical model has been predicted for the delamination at tool entry. The relationship between the machining variables and output variables is also established.